Identification of Predominant User Behavior on the Website and Its Impact on Designing Website Elements - Bartoš, Petr; Stříteský, Václav; Eger, Ludvík; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Understanding user behavior on websites and their interaction with web elements is crucial for proper website design and optimizing conversion paths, layout of page elements, and content placement in terms of usability and aesthetics. The dissertation aims to identify prevalent user behavior traits on websites and typical specifics of this behavior with potential implications for website design, arrangement of web elements, and content on web pages. The dissertation examines selected factors influencing user behavior on websites and how users behave during web browsing – how users utilize their memory, their ability to mentally recall information from web pages, how users visually perceive websites in terms of usability and aesthetics, how users scroll through a webpage, how users read on web pages and interact with active web elements. The dissertation presents the most commonly used research methods in usability testing of web pages. The work includes research on website user behavior and how UX designers approach this behavior in web and application design. The data collection methods were: 1. experiment investigating memory and four main phenomena related to the immediate recall of visual elements on the web – list-length effect, serial position effect, horizontal versus vertical presentation of information, expression of information in the form of symbols, text, and symbols with text; 2. Questioning (In-depth interviews with UX designers to ascertain the rules and principles followed by UX designers in designing web pages and applications). The research results indicate that memory performance in the recall experiment declined as the number of items increased, highlighting the challenges of memory retention, with recall rates decreasing from 92% for 5 items to 67% for 9 items. Interestingly, layout orientation (horizontal vs. vertical) did not significantly affect recall, but combining symbols and text proved the most effective format.
Furthermore, a gender-based analysis revealed that men recalled more items than women. The qualitative analysis of interviews with UX designers suggests a ".CAD" (=DOTCAD) framework and recommendations for proper designing web and app design. This framework underscores the importance of user-friendly designs to reduce cognitive load, considering factors like user intent, mood, and reading behavior. This research's insights can greatly enhance future web and app designs. The findings in the dissertation provide valuable insights for UX designers, offering a roadmap to enhance user experiences, improve usability, and reduce cognitive overload. Incorporating these research-based schemas and principles into design processes can greatly impact the effectiveness of future web and app designs, leading to more user-friendly and engaging digital experiences.
Vedoucí práce: Václav Stříteský
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations